Changes in corneal endothelial cell density in patients with primary open-angle glaucoma - خلوف, علي; تيم درويش ,; حبيب يوسف , (Latakia University Journal -Medical Sciences Series, 2023)
AIM To investigate changes in corneal endothelial cell density in patients with Primary open angle glaucoma (POAG). METHODS A case control study was performed on 68 eyes of 34 patients with POAG. Exclusion criteria included history of corneal diseases, intraocular diseases,contact lens use, ocular trauma or surgery (including intraocular surgery and laser treatment), congenital abnormalities or systemic diseases such as diabetes. Intraocular pressure was measured using Goldmann tonometry. Non contact specular microscopy (Perseus, Cso, Italy) was performed on central cornea and endothelial images were acquired. Endothelial cell density (ECD), and hexagram (EX%), coefficient of variation (CV) were analyzed. RESULTS The POAG eyes had significantly lower endothelial cell density compared to healthy control eyes (P < 0.001). The eyes receiving medication had significantly lower endothelial cell density compared to untreated eyes (P<0.001). There was a negative correlation between cell density and mean IOP as the intraocular pressure increases ,the number of corneal endothelial cells decreases. There was a positive correlation between the average cell area and mean IOP . The percentage of hexagonal cells was not correlated with mean IOP(P>0.001). CONCLUSION Patients with POAG have lower corneal endothelial cell density than healthy controls of the same age. This may be attributed to mechanical damage from elevated IOP and toxicity of glaucoma medications.